A snicker of magic - Lloyd, Natalie (New York : Scholastic Press, 2014)
The Pickles are new to Midnight Gulch, Tennessee, a town which legend says was once magic--but Felicity is convinced the magic is still there, and with the help of her new friend Jonah the Beedle she hopes to bring the magic back.
Keywords: Single-parent families -- Tennessee -- Juvenile fiction; Domestic fiction